WALISONGO ISLAMIC EDUCATION (CULTURAL ACCULTURATION APPROACH) - Waluyo Waluyo; Muhammad Amiruddin Dardiri (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
Nusantara, especially Javanese, before the arrival of Walisongo, was culturally and religiously thick with beliefs passed down from ancestors.  Religious education, in particular, has not been well organized. Java is reflected in the unorganized condition of society in terms of clothing, food, and shelter. Islam in Java was spread during the collapse of the Majapahit kingdom, then the Demak kingdom was established. This era is a transitional period of religious, political, and artistic life. For people who are Muslims, there are several levels, one of which is the guardian as a spiritual leader at the top level. Almost all Islamic education in Java refers to walisongo, although many still consider it fictitious. Some opinions are related to this because there is no historical evidence as a form of the fact of existence and education. This research focuses on the nature of Walisongo's reality and the transformation patterns of education. The ontological approach, in this case, examines the existence of Walisongo in terms of its existence and Islamic education. The essence of Walisongo's education is contained in the fibers of Prince Bonang or Het Book van Bonang and Kropak Ferrara. FiberPrince Bonang and kropak ferrara prove that Walisongo is a fact. The above text shows the truth and existence of Walisongo in terms of Islamic education.